DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON PROBLEM BASED LEARNING IN CLASS V THEMATIC LEARNING AT SD SWATA MARKUS MEDAN - Paskah Apryanti Pakpahan; Sugiharto Sugiharto; R. Mursid R. Mursid (SENSEI RESEARCH CENTER, 2021)
This research and development aim to: (1) produce interactive multimedia based on problem based learning that is suitable for use in the sub-theme of national events during the colonial period, and (2) determine the improvement of student learning outcomes from the use of interactive multimedia based on problem-based learning in the sub-theme of national events, developed colonial period. This type of research is research and development that uses a 4-D model. The research method consists of two stages: the first stage of developing learning multimedia and the second stage of testing the product's effectiveness. The results of the research in the development stage of learning multimedia products show that: (1) the assessment of material experts is in the very feasible criteria with an average score of 4.58, (2) the assessment of media experts is in the very feasible criteria with an average score of 4.51. The effectiveness of the learning device was concluded based on the post-test results of students in the second trial, the percentage of classical completeness was 90% with 30 students or 90% declared complete. Moreover, 3 students or 10% are declared incomplete. 3) The practicality of student learning media is concluded based on the teacher's response; the teacher's response to the learning media in the first trial reached 91.67%, which was included in the convenient category. Assessment of student learning outcomes based on pretest and post-test analyzed using N-Gain obtained an average gain value of 0.7, which is in the high category.